2015
DOI: 10.1371/journal.pone.0129399
|View full text |Cite
|
Sign up to set email alerts
|

The miRNA Profile of Platelets Stored in a Blood Bank and Its Relation to Cellular Damage from Storage

Abstract: Millions of blood products are transfused each year, and many lives are directly affected by transfusion. Platelet concentrate (PC) is one of the main products derived from blood. Even under good storage conditions, PC is likely to suffer cell damage. The shape of platelets changes after 5 to 7 days of storage at 22°C. Taking into consideration that some platelet proteins undergo changes in their shape and functionality during PC storage. Sixteen PC bags were collected and each PC bag tube was cut into six equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…As the miRNA post‐transcriptional control pathway is active in platelets, the effects of post‐collection processing and storage on the miRNA profile of PCs are of interest. It has been suggested that specific miRNA expression patterns can be used to monitor cellular damage related to PSL . Studies looking at miRNAs during platelet storage have shown high levels of miRNAs associated with apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the miRNA post‐transcriptional control pathway is active in platelets, the effects of post‐collection processing and storage on the miRNA profile of PCs are of interest. It has been suggested that specific miRNA expression patterns can be used to monitor cellular damage related to PSL . Studies looking at miRNAs during platelet storage have shown high levels of miRNAs associated with apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A few publications have focused on miRNA in stored platelets, showing differences in the regulation of miRNAs during storage and describing the effects of post‐collection processing methods like PI . It has even been suggested that specific miRNA patterns could predict the quality of stored PCs and that manipulation of the miRNA gene regulation pathway could lead to more effective storage of platelets . Research on miRNAs in stored PCs could contribute to better quality and prolonged shelf life of stored platelets …”
mentioning
confidence: 99%
“…That said, there are downfalls of analyzing the miRNA composition of whole blood as compared to serum, plasma or exosomes. Whole blood contains not only miRNAs from the target tissues, but also miRNAs from each individual cellular components of blood including erythrocytes [19], leukocytes [20] and platelets [21]. The miRNAs derived from the cellular components of blood provide background noise, making it more difficult to identify changes in placental-derived miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these pro apoptosis miRNA are further upregulated during the storage period and some are downregulated . One publication suggests using specific miRNA to monitor the cellular damage related to the PSL . A research group led by Dr. Provost has studied the effects of Intercept treatment on platelet transcriptome (miRNA and mRNA).…”
Section: Microrna Analysis and Platelet Storagementioning
confidence: 99%